PENGARUH HARGA, LOKASI, DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA PERUMAHAN MURAH DI HADRAH PROPERTY - Nabila Mariska Iskandarsyah, Sorayanti Utami (Departemen Manajemen, 2017)
This study aims to determine the effect of Price, Location and Facilities on Consumer Satisfaction at low price housing in Hadrah Poperty. This research use probability sampling and the method used is proportional sampling. The respondend is consumer who has bought house at Hadrah Property. The questionnaire was used as a research instrument for this research method with the number of respondents as much as 120 respondents. Multiple Linear Regression is used to test and analyze hypotheses. The results of this study indicate that the variable price and facilities have a significant effect (sig 0.05) on customer satisfaction, while Location has no significant effect on Consumer Satisfaction (sig 0,05).Key Word: Customer Satisfaction, Price, Location, Facility